A intuição na formação acadêmica do administrador - Gomides, Renato de Castilho (2007)
This dissertation present search to identify the intuition, being a component important of the administrative decisions, always present in the academic formation of the managers and as it would be manifested in that context. For the study was carried out field work, by means of 44 mixed questionnaires with the EBAPE/FGV professors. The facts were treated quantitative, with the construction of tables that permitted us infer about the matter, and qualitative, utilizing the approach of analysis of the content. The study identifies that the intuition is present in the decisive trial and in the managerial decision-making, however with this development have not been consubstantiality in the academic formation of the manager. Of that way, it is necessary a new way think in the construction of the knowledge and in the administrative education, enabling an academic formation more holistic, that attend to the yearnings and the needs of the society, with severity and relevance.